The Landscape of DNA Methylation Associated With the Transcriptomic Network of Intramuscular Adipocytes Generates Insight Into Intramuscular Fat Deposition in Chicken - Meng Zhang; Donghua Li; Yanhui Zhai; Zhengzhu Wang; Xiangfei Ma; Daoyu Zhang; Guoxi Li; Ruili Han; Ruirui Jiang; Zhuanjian Li; Xiangtao Kang; Guirong Sun (Frontiers in Cell and Developmental Biology, 2020)
Intramuscular fat (IMF), which regulated by genetics, nutrition and environment is an important factor that influencing meat quality. Up to now, the epigenetic regulation mechanism underlying poultry IMF deposition remains poorly understood. Here, we focused on the DNA methylation, which usually regulate genes in transcription level. To look into the essential role of DNA methylation on the IMF deposition, chicken intramuscular preadipocytes were isolated and cultured in vitro, and a model of intramuscular adipocyte differentiation was constructed. Combined the whole genome bisulfite sequencing (WGBS) and RNA-Seq technologies, we identified several methylated genes, which mainly affecting fatty acid metabolism and muscle development. Furthermore, we reported that DNA methylation regulate intramuscular adipogenesis by regulating the genes, such as collagen, type VI, alpha 1 (COL6A1) thus affecting IMF deposition. Overexpression of COL6A1 increases the lipid droplet and inhibits cell proliferation by regulating CHAD and CAMK2 in intramuscular adipocytes, while knockdown of COL6A1 shows the opposite effect. Taken together, our results reveal that DNA methylation plays an important role in poultry IMF deposition.